2008
DOI: 10.2353/ajpath.2008.070930
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Plasminogen Activator Inhibitor Type-1 in Radiation Enteropathy

Abstract: Intestinal radiation injury is a dose-limiting factor in radiation therapy for abdominal and pelvic cancers. Because transforming growth factor-␤1 is a key mediator involved in radiation-induced damage, we hypothesized that its target gene, plasminogen activator inhibitor type 1 (PAI-1), is an essential mediator of intestinal radiation toxicity. In a model of radiation enteropathy, survival was monitored and intestinal radiation injury was assessed in both wild-type (Wt) and PAI-1 knockout mice. Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 32 publications
5
56
0
4
Order By: Relevance
“…Additionally, PAI-1 over-expression is observed in radiation-induced nephrosclerosis [32] and in human radiation enteritis and intestinal lesion [33,34] underlining a role for PAI-1 in radiation-induced tissue damages. Interestingly, PAI-1 knockout mice are protected against radiation-induced intestinal damage [34]. We confirmed and extended these findings by showing that PAI-1 contributes to the acute response of the endothelium to ionizing radiation, and it inhibits the angiogenic response in the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PAI-1 over-expression is observed in radiation-induced nephrosclerosis [32] and in human radiation enteritis and intestinal lesion [33,34] underlining a role for PAI-1 in radiation-induced tissue damages. Interestingly, PAI-1 knockout mice are protected against radiation-induced intestinal damage [34]. We confirmed and extended these findings by showing that PAI-1 contributes to the acute response of the endothelium to ionizing radiation, and it inhibits the angiogenic response in the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ionizing radiation was shown to increase PAI-1 expression in NRK52E [30] and HEPG2 cells [31]. Additionally, PAI-1 over-expression is observed in radiation-induced nephrosclerosis [32] and in human radiation enteritis and intestinal lesion [33,34] underlining a role for PAI-1 in radiation-induced tissue damages. Interestingly, PAI-1 knockout mice are protected against radiation-induced intestinal damage [34].…”
Section: Discussionmentioning
confidence: 99%
“…Localized small intestinal radiation injury was induced by exposure of an intestinal segment to 19 Gy of radiation (7). Briefly, TGIF1…”
Section: Methodsmentioning
confidence: 99%
“…Radiation-induced up-regulation of TGF-␤1 expression levels has been shown in various organs, and, in addition to TGF-␤1 itself, several studies have shown up-regulation of intracellular effectors of TGF-␤1 signaling, in particular the canonical Smad-dependent pathway (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Ce dernier diminue, par conséquent, le taux de plasmine et la fibrinolyse, favorisant la thrombose vasculaire. Les souris génétiquement déficientes en PAI-1 sont protégées contre les lésions digestives radioinduites [21]. Éviter l'augmentation radio-induite de la synthèse de PAI-1 ou utiliser des inhibiteurs de PAI-1 pourrait limiter les dommages intestinaux radio-induits.…”
Section: Quand La Cicatrisation S'emballe : De L'inflammation Aiguë àunclassified